2004
DOI: 10.1158/0008-5472.can-04-1776
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Macrophage Colony-Stimulating Factor and Interleukin-2 Fusion cDNA for Cancer Gene Immunotherapy

Abstract: Genetic engineering of tumor cells to express both granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin (IL)-2 can induce synergistic immune antitumor effects. Paradoxically, the combination has also been reported to down-regulate certain immune functions, highlighting the unpredictability of dual cytokine use. We hypothesized that a GM-CSF and IL-2 fusion transgene (GIFT) could circumvent such limitations yet preserve synergistic features. We designed a fusion cDNA of murine GM-CSF and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 19 publications
1
44
0
3
Order By: Relevance
“…1C). Furthermore, we have previously demonstrated that the N-terminal GM-CSF component of two distinct fusokines (GIFT2 and GIFT15) will bind to GM-CSF receptor and will act as a mitogen for GM-CSF-dependent JAWSII cells and will also lead to normal downstream signaling (as represented by STAT5 phosphorylation) akin to monomeric GM-CSF (10,11). We were unable to make similar analysis of GMME1 due to its pro-apoptotic properties on JAWSII cells in vitro (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1C). Furthermore, we have previously demonstrated that the N-terminal GM-CSF component of two distinct fusokines (GIFT2 and GIFT15) will bind to GM-CSF receptor and will act as a mitogen for GM-CSF-dependent JAWSII cells and will also lead to normal downstream signaling (as represented by STAT5 phosphorylation) akin to monomeric GM-CSF (10,11). We were unable to make similar analysis of GMME1 due to its pro-apoptotic properties on JAWSII cells in vitro (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…GM-CSF was selected as the N-terminal partner because it is permissive for high fusokine secretion by transfected cells (10,11). Furthermore, GM-CSF has a fairly long plasma half-life reported to be ϳ6 h (12,13), which may markedly extend the in vivo bioavailability of C-terminal domains such as truncated CCL2.…”
Section: R Heumatoid Arthritis (Ra)mentioning
confidence: 99%
“…To evaluate whether the distinct GM-CSF and IL-2 domains of GIFT-2 were functional, GIFT-2 was applied to the JAWSII and CTLL-2 cell lines to evaluate whether the fusokine could replicate GM-CSF's and IL-2's respective abilities to induce their proliferation. IL-2 was as effective as its unfused counterparts at maintaining these cells lines in culture; however, contrary to pIXY 321, GIFT-2 did not significantly enhance their proliferation (41). In vitro investigations into GIFT-2's ability to mediate tumor rejection in mice found that GIFT-2-stimulated NK cells adopted a novel proinflammatory phenotype (42); these NK cells produced significantly more IFN-g than did cells treated with GM-CSF, IL-2, or the combination of the two, and they were highly cytolytic and resistant to GM-CSF's regulatory effects (43).…”
Section: Combining Cytokines To Target Distinct Immune Cellular Subsetsmentioning
confidence: 70%
“…Despite the overlapping functions of their source material, the GIFTs differed remarkably from one another in terms of their signaling and their net effects. GIFT-2 retained an IL-2-like phenotype, but with the hyperinduction of STAT1, STAT3, and STAT5 (41). GIFT-15 completely altered IL-15R signaling because it induced a hyperphosphorylation of STAT3 and a hypophosphorylation of STAT5 (44) We speculate that GIFT-15's higher affinity for the IL-15Ra-chain and the GM-CSF moiety have altered receptor-binding properties in terms of how GIFT-15 fits into the IL-15-binding cleft (44), but it is not obvious how this alters the phosphorylation of Jaks and STATs further downstream.…”
Section: Combining Cytokines To Target Distinct Immune Cellular Subsetsmentioning
confidence: 97%
“…GM-CSF is a hematopoietic growth factor that stimulates neutrophil, monocyte/macrophage, and eosinophil colony formation, and has been applied in a variety of clinical and research settings (14,16). GM-CSF can elicit high cytotoxic T cell immune response in DNA vaccine against hepatitis C virus (HCV, 23), tuberculosis (TB, 33) and tumors (29).…”
mentioning
confidence: 99%